Industry Perspectives on Digital Competences Among MBKM Interns in Indonesia - Linasari Santioso (Return : Study of Management, Economic and Bussines, 2024)
Indonesia's digital economy is expanding at a breakneck pace, highlighting the urgent need for digital competencies that align with industry demands. Addressing this critical issue, the Ministry of Education, Culture, Research, and Technology of Indonesia has initiated the Merdeka Belajar Kampus Merdeka (MBKM) program, one of the programs, emphasizing practical internships to enhance undergraduates' digital skills.This research aims to examine the effectiveness of the MBKM initiative in narrowing the disparity between graduates' digital competencies and the evolving needs of various industries, shedding light on the program's role in fostering digital readiness among undergraduatesThis research scrutinizes the impact of the MBKM initiative on bridging the gap between graduates' digital competencies and the expectations of diverse industries. It specifically assesses the efficacy of the program in cultivating essential digital skills through IT-related tasks in various sectors. Employing a Likert-scale questionnaire rooted in the DigComp 2.0 framework, the research surveyed host companies across Jakarta, evaluating the digital proficiency of MBKM interns and their readiness for employment. Analysed through the Smart PLS, the research employed PLS-SEM to unravel the influence of digital competencies on employability. Findings indicate that one digital competence, Digital Content Creation, is significantly associated with employability prospects. Conversely, Information and Data Literacy, Communication and Collaboration, Safety, and Problem Solving did not exhibit a substantial direct effect on employability. This research underlines the critical nature of enhancing specific competencies within the MBKM framework to better prepare Indonesia's workforce for the demands of a digital future. The insights gleaned offer strategic implications for refining educational programs and underscore the importance of continual alignment with industry needs, thereby strengthening the nation's digital talent pool.